What Caused the 1991 Currency Crisis in India? - Saxena, Sweta (IMF Working Papers; Working Paper ;, 2000)
Did real overvaluation contribute to the 1991 currency crisis in India? This paper seeks an answer by constructing the equilibrium real exchange rate, using an error correction model and a technique developed by Gonzalo and Granger (1995). The results are affirmative and the evidence indicates that current account deficits and investor confidence also played significant roles in the sharp exchange rate depreciation. The ECM model is supported by superior out-of-sample forecast performance versus a random walk model.